Role of the mu 1 protein in reovirus stability and capacity to cause chromium release from host cells. - Hooper, J W (1996)
The reovirus M2 gene is associated with the capacity of type 3 strain Abney (T3A) intermediate subviral particles (ISVPs) to permeabilize cell membranes as measured by chromium (51Cr) release (P. Lucia-Jandris, J. W. Hooper, and B. N. Fields, J. Virol. 67:5339-5345, 1993). In addition, reovirus mutants with lesions in the M2 gene can be selected by heating virus at 37 degrees C for 20 min in 33% ethanol (D. R. Wessner and B. N. Fields, J. Virol. 67:2442-2447, 1993). In this report we investigated the mechanism by which the reovirus M2 gene product (the mu 1 protein) influences the capacity of reovirus ISVPs to permeabilize membranes, using ethanol-selected T3A mutants. Each of three T3A ethanol-resistant mutants isolated (JH2, JH3, and JH4) exhibited a decreased capacity to cause 51Cr release relative to that of wild-type T3A. Sequence analysis of the M2 genes of wild-type T3A and the T3A mutants indicated that each mutant possesses a single amino acid substitution in a central region of the 708-amino-acid mu 1 protein: JH2 (residue 466, Tyr to Cys), JH3 (residue 459, Lys to Glu), and JH4 (residue 497 Pro to Ser). Assays performed with reovirus natural isolates, reassortants, and a set of previously characterized type 3 strain Dearing (T3D) ethanol-resistant mutants revealed a strong correlation between ethanol sensitivity and the capacity to cause 51Cr release. We found that ISVPs generated from the T3A and T3D mutants were stable when heated to 50 degrees C, whereas wild-type T3A ISVPs are inactivated under these conditions. Together, these data suggest that amino acid substitutions in a central region of the mu 1 protein affect the capacity of the ISVP to permeabilize L-cell membranes by altering the stability of the virus particle.